2015
DOI: 10.2147/dddt.s87131
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for an individualized pharmacogenetic-guided isoniazid dosage regimen for patients with tuberculosis

Abstract: Background/aimIsoniazid (INH) is an essential component of first-line anti-tuberculosis (TB) treatment. However, treatment with INH is complicated by polymorphisms in the expression of the enzyme system primarily responsible for its elimination, N-acetyltransferase 2 (NAT2), and its associated hepatotoxicity. The objective of this study was to develop an individualized INH dosing regimen using a pharmacogenetic-driven model and to apply this regimen in a pilot study.MethodsA total of 206 patients with TB who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 17 publications
2
46
1
Order By: Relevance
“…Although the use of TDM in the treatment of patients with tuberculosis has become more widely accepted (23)(24)(25)(26), there are few reports of the clinical usefulness of TDM in patients with NTM lung disease (13)(14)(15). We previously reported that low plasma CLR concentrations were common in patients treated for MAC-LD, although we found no association between low plasma CLR concentrations and treatment outcomes (14).…”
Section: Discussioncontrasting
confidence: 55%
“…Although the use of TDM in the treatment of patients with tuberculosis has become more widely accepted (23)(24)(25)(26), there are few reports of the clinical usefulness of TDM in patients with NTM lung disease (13)(14)(15). We previously reported that low plasma CLR concentrations were common in patients treated for MAC-LD, although we found no association between low plasma CLR concentrations and treatment outcomes (14).…”
Section: Discussioncontrasting
confidence: 55%
“…Although the acetylation polymorphism of NAT2 enzyme was discovered over 50 years ago following differences observed in TB patients to INH toxicity such as the occurrence of peripheral neuritis [13], in later studies the NAT2 slow acetylator genotype was proposed be a significant risk factor for ATLI [14e18]. Moreover, it was shown that individual dosing of INH according to NAT2 status improved treatment and reduced side effects [19,20]. The status of NAT2 activity depends on the number of active alleles (NAT2*4, *12 and *13), and a slow acetylator phenotype is generally observed for individuals with two germ-line copies of alleles that contain any of several single-nt substitutions [3,21].…”
Section: Introductionmentioning
confidence: 99%
“…8 This is due to genetic acetylation polymorphism phenomena, which has both therapeutic and toxic consequences. The patients with lower blood levels acetylate the drug more rapidly while those with higher level of INH acetylate it more slowly.…”
Section: Isoniazid Metabolism Mode Of Action and Toxicitymentioning
confidence: 99%
“…However, it is worth appreciating that slow acetylators had a higher risk of ATLI and it is acknowledged that knowledge of patient"s phenotype will be useful for the clinical prediction and prevention of ATLI. [8][9][10] Fast and slow acetylator statuses are inherited in simple Mendelian manner with the fast acetylation gene being autosomal dorminant. 11 This accounts for the difference in acetylation rate among individuals and ethnic groups, and thus the variation in blood levels of INH.…”
Section: Isoniazid Metabolism Mode Of Action and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation